Pendeteksian Financial Statement Fraud melalui Komponen Fraud Triangle - Nurul Aini; Eman Sukanto (JAAF (Journal of Applied Accounting and Finance), 2021)
The aim of this study is deemed to analyze the influence of fraud triangle as a tool to detect the fraud in a financial statement. The research focuses on the trading sector companies from 2014 to 2016 that are listed on the Indonesia Stock Exchange. After selecting these companies, 24 of them become the definite samples. They are divided into companies that are probable doing financial statement fraud and those which are not based on the model of Beneish M-Score. For that, this research uses logistic regression. The results show that those that have significant effect on financial statement fraud are external pressure, ineffective monitoring, and financial stability. And those insignificant variables include auditor change, financial target, and the nature of industry.